Deceptive nature of Dial-a-Porn commercials and public policy alternatives - Borna, Shaheen (Journal of business ethics, 1993)
This research investigates consumers' perceptions of claims made in Dial-a-Porn commercials. The empirical findings support the view that some of the claims are deceptive. Based on research findings, preliminary public policy guidelines are suggested.